Guidelines for Editing Biomedical Journals: Recommended by Academy of Medical Sciences of Bosnia and Herzegovina - Masic, Izet (Acta Inform Med, 2020)
BACKGROUND: Enormous number of medical journals published around the globe requires standardization of editing practice. OBJECTIVE: The aim of this article was to enlist main principles of editing biomedical scientific journals adopted at annual meeting of Academy of Medical Sciences of Bosnia & Herzegovina (AMSB&H). METHODS: The evidence for writing this Guideline was systematically searched for during September 2020 in the PUBMED and GOOGLE SCHOLAR databases. The inclusion criteria were: original studies, systematic reviews, invited expert opinions, guidelines and editorials. The exclusion criteria were narrative reviews and uninvited opinion articles. The retrieved evidence was analyzed by members of the AMSB&H, then discussed at 2020 annual meeting of the AMSB&H and adopted by nominal group technique. RESULTS: In total 14 recommendations were made, based on A to C class of evidence. The editors should educate potential authors and instruct them how to structure their manuscript, how to write every segment of the manuscript, and take care about correct use of statistical tests. Plagiarism detection softwares should be used regularly, and statistical and technical editing should be rigorous and thorough. International standards of reporting specific types of studies should be followed, and principles of ethical and responsible behavior of editors, reviewers and authors should be published on the journal’s web site. The editors should insist on registration of clinical studies before submission, and check whether non-essential personal information is removed from the articles; when essential personal information has to be included, an article should not be published without signed informed consent by the patient to whom these information relate. CONCLUSIONS: Principles of editing biomedical scientific journals recommended in this guideline should serve as one of the means of improving medical journals’ quality.